2019
DOI: 10.1002/oby.22369
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity in Response to Treatment of Adolescents with Severe Obesity: The Need for Precision Obesity Medicine

Abstract: Objective: Treating pediatric severe obesity is challenging because of the complex biological, behavioral, and environmental factors that underpin the disease. The multifactorial etiology of obesity combined with the physiologic complexity of the energy regulatory system contributes to treatment variability. The goal of this secondary analysis of pooled data was to describe the degree of individual variation in response to various interventions among adolescents with severe obesity. Methods: Data from three ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 34 publications
1
37
0
Order By: Relevance
“…When looking at change in BMI of the study participants at the individual level, a heterogeneous response was evident. This emphasizes the importance to study individual outcomes in order to effectively treat adolescents with obesity …”
Section: Discussionmentioning
confidence: 99%
“…When looking at change in BMI of the study participants at the individual level, a heterogeneous response was evident. This emphasizes the importance to study individual outcomes in order to effectively treat adolescents with obesity …”
Section: Discussionmentioning
confidence: 99%
“…A total of 36 studies were found that met the search criteria. The majority of studies were reviews ( n = 16, Table ), 8 were observational, 7 were case‐control studies, 3 were quasi‐experimental/case‐control studies, and 2 were RCTs (1 was a methods paper only) (Table ). No studies that tested the combination of pharmacotherapy interventions with MBS were found.…”
Section: Resultsmentioning
confidence: 99%
“…Other reviews included the importance of the preoperative assessment tools and postoperative multidisciplinary teams (e.g., dietitian, social worker, psychologist) , clinical dietary recommendations , and cosmetic (e.g., skin) considerations, but none did so in a theoretical framework or by citing evidence‐based findings from previously successful secondary prevention lifestyle interventions. The three review papers that included pharmacotherapy support interventions highlighted the need for more research focused on combination therapies (MBS, pharmacotherapy, lifestyle) to support precision medicine treatment approaches among adolescents with severe obesity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These external factors will affect the weight loss intervention, as well as its maintenance in the long term [68,69]. Besides, there is a high degree of heterogeneity in the impact of these factors both, during and after a weight intervention [70]. In principle, the modelling framework developed in this study cannot provide directly any information…”
Section: Current Limitations and Future Perspectivesmentioning
confidence: 99%